Pain mechanisms in the transgender individual: a review - Anger, Jennifer T.; Case, Laura K.; Baranowski, Andrew P.; Berger, Ardin; Craft, Rebecca M.; Damitz, Lyn Ann; Gabriel, Rodney; Harrison, Tracy; Kaptein, Kirsten; Lee, Sanghee; Murphy, Anne Z.; Said, Engy; et al. (Frontiers in Pain Research, 2024)
Specific Aim Provide an overview of the literature addressing major areas pertinent to pain in transgender persons and to identify areas of primary relevance for future research. Methods A team of scholars that have previously published on different areas of related research met periodically though zoom conferencing between April 2021 and February 2023 to discuss relevant literature with the goal of providing an overview on the incidence, phenotype, and mechanisms of pain in transgender patients. Review sections were written after gathering information from systematic literature searches of published or publicly available electronic literature to be compiled for publication as part of a topical series on gender and pain in the Frontiers in Pain Research. Results While transgender individuals represent a significant and increasingly visible component of the population, many researchers and clinicians are not well informed about the diversity in gender identity, physiology, hormonal status, and gender-affirming medical procedures utilized by transgender and other gender diverse patients. Transgender and cisgender people present with many of the same medical concerns, but research and treatment of these medical needs must reflect an appreciation of how differences in sex, gender, gender-affirming medical procedures, and minoritized status impact pain. Conclusions While significant advances have occurred in our appreciation of pain, the review indicates the need to support more targeted research on treatment and prevention of pain in transgender individuals. This is particularly relevant both for gender-affirming medical interventions and related medical care. Of particular importance is the need for large long-term follow-up studies to ascertain best practices for such procedures. A multi-disciplinary approach with personalized interventions is of particular importance to move forward.